The Psychosocial Ramifications of Videogame Naming and Representation in the Early Years of The Simpsons. (December 2015) - Butler, James O.
Abstract : The Simpsons is a parody of suburban American life, and, as one member of the titular family is a 10-year-old boy, videogames make a number of appearances. This article is a comprehensive overview of every occurrence or reference to gaming made within the first decade (1989–1999), and will assess the stereotypical aspects of both games and gamers made throughout the series. The majority of entries are not actively depicted on screen, but provide names that match the exaggerated over-the-top violent nature of those that are, which forms a consistent satirical depiction of the hobby. This study seeks to add a new voice to the argument for names possessing semantic content, especially artistic onyms, in the ongoing critical debate.